A Bibliometric Analysis of Foreign Workers and Construction Development in the Current Era - Agung Wibowo, M.; Agustinus Purna Irawan; Rahim Awang, Abd (Dinasti Research, 2024)
This study aims to examine the trends of research on Foreign Workers and Construction Development in the Current Era from 2012 to 2022. This research used qualitative research methodology with a bibliometric analysis approach. The primary data of this research was collected through the Scopus database with identifying articles/journals related to the topics of Foreign Workers and Construction Development. This study also uses VOS Viewer to visualize and analyze the primary data with network and density calculation. The result of this study is Russia became the first country to produce many articles from 2012 to 2022. Furthermore, the Engineering is the highest source of publication. Then, most researchers used quantitative methods with online surveys dominantly in the publications related to the topic. Topics about Construction Development, Construction Industry, and Foreigner Worker have the most frequent occurrences and the highest total link strength in the network. Besides, construction development, construction activities, construction industry, etc., have a big opportunity for conducting in the future in terms of foreign workers and construction development in the current era. This study successfully explained global research trends related to foreign workers and construction development in the current era from 2012 to 2022. However, this study has limitations in terms of data sources because the Scopus database is a closed access resource.